2021
DOI: 10.3390/app11094305
|View full text |Cite
|
Sign up to set email alerts
|

Surface Functionalization of PLGA Nanoparticles to Increase Transport across the BBB for Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a chronic neurodegenerative disorder that accounts for about 60% of all diagnosed cases of dementia worldwide. Although there are currently several drugs marketed for its treatment, none are capable of slowing down or stopping the progression of AD. The role of the blood-brain barrier (BBB) plays a key role in the design of a successful treatment for this neurodegenerative disease. Nanosized particles have been proposed as suitable drug delivery systems to overcome BBB with the purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 184 publications
0
16
0
Order By: Relevance
“…Regarding charge effects, brain microvascular endothelial cells have a net negative surface charge, thus repelling negatively charged compounds. 116 DLS results indicate that large size NPs have more negative charges on the surface (Table 1). Therefore, large size FA-loaded PLGA_Flu NPs having more negative charges, are expected to experience an added difficulty in crossing the BBB.…”
Section: Blood-brain Barrier Membrane Model (Bbb-oc)mentioning
confidence: 99%
“…Regarding charge effects, brain microvascular endothelial cells have a net negative surface charge, thus repelling negatively charged compounds. 116 DLS results indicate that large size NPs have more negative charges on the surface (Table 1). Therefore, large size FA-loaded PLGA_Flu NPs having more negative charges, are expected to experience an added difficulty in crossing the BBB.…”
Section: Blood-brain Barrier Membrane Model (Bbb-oc)mentioning
confidence: 99%
“…The surface decoration of PLGA NPs with polyethylene glycol (PEG) has been reported to have many advantages, such as (i) improving the water solubility of the PLGA NPs and their hydrophobic cargos, (ii) increasing the surface charge and the steric hindrance on the PLGA NPs thus extending the stability of the NPs and minimizing their aggregation, (iii) causing a stealth effect that prolongs the systemic circulation duration of drugs via inhibiting the opsonization effect, and (iv) enhancing the release of the drugs out of the polymeric matrix [23,24]. Many studies have reported using PEGylated PLGA NPs as promising nanocarriers for various natural bioactive compounds, biotherapeutics (as peptides, proteins, or vaccines), and synthetic drugs [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this goal, many nanocarrier systems, such as inorganic, polymeric, or lipid-based nanoparticles, have been developed and shown to cross the BBB due to their tailored surface properties. Numerous studies have demonstrated that physically coating nanoparticles with surfactants and chemical functionalization with specific ligands is a successful strategy to enhance BBB traversing via the physiological pathways mentioned above [ 39 , 40 ]. The size and charge of nanoparticles are also aspects that can affect brain penetration, but if the surface functionalization is done properly, there is no significant difference in a wide size range (from 5 to 400 nm) [ 41 ].…”
Section: Strategies To Improve Permeability Of Nanocarrier Through the Blood-brain Barriermentioning
confidence: 99%